2016
DOI: 10.1080/00036846.2016.1205721
|View full text |Cite
|
Sign up to set email alerts
|

An increase in the retirement age in China: the regional economic effects

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…At the same time as demand is rising, the supply of informal care provision from grandparents is coming under pressure as the government is considering a major reform to increase the retirement age in the face of population ageing (Chen and Groenewold, 2017). If both mid-life women and men have to remain in the labour market for longer, fewer members of the sandwich generation will be available to provide informal care to either the younger or older generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time as demand is rising, the supply of informal care provision from grandparents is coming under pressure as the government is considering a major reform to increase the retirement age in the face of population ageing (Chen and Groenewold, 2017). If both mid-life women and men have to remain in the labour market for longer, fewer members of the sandwich generation will be available to provide informal care to either the younger or older generation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a growing number of individuals in China face the possibility in mid-life of being ‘sandwiched’ between the provision of care to their own older parents/parents-in-law and also to their younger grandchildren. Understanding how this so-called ‘sandwich generation’ divides their resources in terms of time between the care of older and younger generations and other activities, including paid employment, is particularly pertinent in a context such as China, where the state remains predominantly dependent on the family for the delivery of care for older people and infant/toddlers (Zimmer and Kwong, 2003; Cong and Silverstein, 2012), and where the government has recently indicated that it plans to increase the retirement age (Chen and Groenewold, 2017), with the result that in the near future, even more individuals in their fifties and early sixties may be faced with the need to juggle work and family responsibilities.…”
Section: Introductionmentioning
confidence: 99%
“…Принимая решение о повышении пенсионного возраста, правительство по-разному может распорядиться сэкономленными средствами. А. Chen, N. Groenewold [29] на примере Китая оценивают макроэкономические последствия двух вариантов: когда эти деньги направляются на финансирование других расходов или на увеличение пенсий (либо снижение взносов). Было установлено, что повышение пенсионного возраста в любом варианте приводит к росту благосостояния граждан, увеличению выпуска и снижению неравенства (как между регионами, так и между гражданами), при этом положительный эффект выше во втором варианте, когда увеличение пенсионного возраста сопровождается ростом пенсионных выплат.…”
Section: экономический эффект старения населения и пенсионных реформunclassified
“…James (2002), and Sun and Suo (2007) note that accumulated savings and private insurance solutions should fill the protection gap of the Chinese public pension, which alone is considered insufficient if the aim is to cover all residents. A few models for analysing reform options for the Chinese public pension system are developed, accompanied by simulations based on macroeconomic statistics, for example Yang (2009), Song et al (2015), and Chen and Groenewold (2017). Wang et al (2014b) empirically estimate the (expected) pension fund gap of China in 2013, 2020, and 2050 based on macroeconomic statistics, and highlight the risk of a Chinese fiscal crisis in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing studies on Chinese retirement preparation use macroeconomic statistics to assess public pension programmes, for example Wang et al (2014a), or use a modelling-simulation approach to derive policy implications on pension reforms, for example Wang et al (2014b), Song et al (2015), and Chen and Groenewold (2017). 5 This study is the first to consider preparation for retirement in China at the microeconomic level.…”
Section: Introductionmentioning
confidence: 99%